Measure words and classifiers - Doetjes, Jenny (Revista Letras, 2017)
This paper investigates the relation between measure words and mensural classifiers in numeral classifier languages. Based on data from three numeral classifier languages (Mandarin, Mokilese and Taba), the paper gives some preliminary evidence that measure words can be both classifier-like and noun-like in numeral classifier languages. This observation is discussed in the light of Rothstein’s (2009, 2011) distinction between measuring and counting, Krifka’s (1995) numeral based analysis of numeral classifier languages and Chierchia’s (1997) proposal of treating nouns in classifier languages as kinds. Crucially, if the measure words are treated as nouns, one has to take into account that the atomic entities corresponding to units of measurement typically overlap. This is problematic for the type of interpretation that Chierchia (1997) assigns to kinds, as the kinds corresponding to different units of time would be indistinguishable. Other approaches will need a non-overlap condition on counting structures.